Enhancement of performance and response time of cascaded vsc statcom in the presence of voltage variation and low power factor - Mohamad Milood, Mohamad Almelian (2022)
The power system is an extremely non-linear system with several interconnected loads. When several loads are suddenly connected at distribution ends or when the power system is subjected to the fault, the stability of the system will be disturbed. The major problems here are the voltage sag, voltage swell and low power factor (PF). A static synchronous compensator (STATCOM) is one of the most effective flexible alternating current transmission systems (FACTS) device that can inject or absorb proper reactive power to retrieve the reliability of the grid-connected systems in presence of mentioned disturbances. STATCOM circuit comprises a control circuit, voltage source converter (VSC), and PWM technique. The STATCOM performance is mainly relying on how accurately and quickly the error signal (input of control unit) is compensated. Various controllers for STATCOM control circuit have been proposed to regulate its performance, artificial neural network (ANN)- based STATCOM control circuit is the dominant and liberal solution for enhancing STATCOM performance during the period of different disturbances. The recent researches are training ANN-based STATCOM upon tackling one or two case of disturbances, which leads to creating a weak and unreliable STATCOM during the period of other disturbances that could happen through normal daily operations, whereby the STATCOM will work in reliability if ANN trains on a different range of operating states. Also, although space vector PWM (SVPWM) that uses with STATCOM is an advanced PWM method and possibly the best among all the PWM techniques, the currently used SVPWM circuit is considered complexity since it requires the calculation of switching time and sector identification. Moreover, even-though the PWM technique and VSC are parts of the STATCOM circuit, there is a lack of investigation on the effect of VSC level and switching frequency on enhancement of performance and response time while tackling disturbances. In this thesis, a developed approach for the STATCOM circuit has been introduced. The proposed STATCOM circuit includes a modified circuit of SVPWM to reduce the implementation complexity in conventional technique, hence minimizing volumetric size, and a reliable ANN control unit able to enhance performance and response time in terms of improving voltage magnitude, power factor (PF) amplitude, and STATCOM current's total harmonic distortion (THD) in the presence of five various types of disturbances, which are voltage sag ( SLG and LL fault case), voltage swell, lagging PF load, and leading PF load. Also, this thesis presented the characteristic responses of affecting factors (VSC level and switching frequency) that enhances STATCOM performance and its response time while tackling aforementioned disturbances. The simulation outcomes showed that the developed STATCOM circuit was able to enhance voltage and PF rapidly in 0.02 sec with THD less than 5% during all disturbances. Moreover, the results of changing the factors from the point of VSC level and switching frequency have proven the possibility of enhancing response time and performance of STATCOM, whereby the response time and improvement in bus voltage increase when the STATCOM based on 5-level VSC rather than 3-level VSC. In contrast, response time decreases without enhancement in voltage when the switching frequency is raising, whereas the PF amplitude and THD value are enhanced once the VSC level and switching frequency increases.